2022
DOI: 10.1101/2022.02.24.481703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial photobiomodulation enhances visual working memory capacity in humans

Abstract: Transcranial photobiomodulation (tPBM) is a novel and noninvasive intervention, which has shown promise for improving cognitive performances. Whether tPBM can modulate brain activity and thereby enhance working memory (WM) capacity in humans remains unclear. In this study, we delivered double-blind and sham-control tPBM with different wavelengths to the prefrontal cortex (PFC) in 90 healthy participants and conducted four electroencephalography (EEG) experiments to investigate whether individual visual working… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This view enables to explain the tPBM-induced augmentation of human cognition in healthy humans besides in patients with brain disorders [26,58,101]. This side of opinions has been supported by several publications [58], and now by two other independent studies that also reported significant improvement of working memory in healthy young [102] and older adults [103] by repeated tPBM. However, the two opinions on the basic mechanism of tPBM have coexisted for years, without one outweighing the other.…”
Section: Two Opinions On Basic Mechanism Of Tpbmmentioning
confidence: 81%
“…This view enables to explain the tPBM-induced augmentation of human cognition in healthy humans besides in patients with brain disorders [26,58,101]. This side of opinions has been supported by several publications [58], and now by two other independent studies that also reported significant improvement of working memory in healthy young [102] and older adults [103] by repeated tPBM. However, the two opinions on the basic mechanism of tPBM have coexisted for years, without one outweighing the other.…”
Section: Two Opinions On Basic Mechanism Of Tpbmmentioning
confidence: 81%
“…One article showed that PBM had no effect on the four major resting-state brain networks, relating to the fact that the subjects were young and healthy, as opposed to other studies. One article showed significant temperature increase Cognitive function [ 8 , 29 , 40 , 41 , 44 , 48 – 51 , 54 , 70 , 81 , 85 , 88 , 93 , 96 , 100 , 104 ] 18 697 645 healthy volunteers. 52 patients Mostly 18–35 years.…”
Section: Resultsmentioning
confidence: 99%